Two new Oribatid mites from Costa Rica, Mixacarus turialbaiensis sp. n. and Paulianacarus costaricensis sp. n. (Acari, Oribatida, Lohmanniidae) - Fernandez, Nestor; Theron, Pieter Daniel; Leiva, Sergio Dante; Tiedt, Louwrens (Pensoft Publishers, 2019)
In this paper we describe two new species belonging to the family Lohmanniidae: Mixacarus turialbaiensis sp. n. and Paulianacarus costaricensis sp. n. from Costa Rica.